Assessing the causal relationships between human blood metabolites and the risk of NAFLD: A comprehensive mendelian randomization study - Guo, Ziwei; Zhang, Tingyu; Yun, Zhangjun; Jin, Qian; Cao, Xu; Kong, Deming; Yao, Yuhao; Li, Xiaoke; Zhang, Jiaxin; Ye, Yong’An (Frontiers in Genetics, 2023)
Abstract Background: Non-alcoholic fatty liver disease (NAFLD) is a liver disease associated with obesity, insulin resistance, type 2 diabetes mellitus (T2DM), and metabolic syndrome. The risk factors for NAFLD have not been identified. Metabolic dysfunction has been found to be an important factor in the pathogenesis and progression of NAFLD. However, the causal impact of blood metabolites on NAFLD is unclear. Methods: We conducted two-sample Mendelian randomization (MR) analysis. Data for 486 human blood metabolites came from a genome-wide association study (GWAS) comprising 7824 participants. Outcome information was obtained from a large-scale GWAS meta-analysis of NAFLD, which contained 8,434 cases and 770,180 controls of Europeans. The inverse variance weighted (IVW) model was used as the primary two-sample MR analysis method and followed the sensitivity analyses, including heterogeneity test, horizontal pleiotropy test, and leave-one-out analysis. In addition, we conducted replication, meta‑analysis, and metabolic pathway analysis.We further conducted colocalization analysis to deeply reflect the causality.Results: After rigorous genetic variant selection, IVW, sensitivity analysis, replication, and meta‑analysis, two known metabolites were identified as being associated with the development of NAFLD [biliverdin: OR= 1.45; 95% CI 1.20-1.75; P = 0.0001; myristoleate: OR=0.57; 95% CI 0.39-0.83; P = 0.0030]. Conclusion: By combining genomics with metabolomics, our findings provide a new perspective on the underlying mechanisms of NAFLD and have important implications for the screening and prevention of NAFLD.